Workshops On Digital Media And Communication For Older People’s Health - Carly Stiana Scheffer Sumampouw (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2018)
Technology illiterate and the physical, mental, cognitive health decline of older people are the main issues this article tries to address. As communication scholars, the teacher and students of FISIP-UPH are working on how digital communication contributes in increasing and maintaining the health of people above 60 years of age. There is a huge gap between different generations in responding to digital media. The reality is digital natives are the teacher while older people become the students in digital communication. The method employs two times of workshops-basic class and intermediate class whilst evaluation happens in the last day. Within these two classes, older people learned certain social media and mobile apps such as: video calls, BPJS online, online drug store, online transportation, PicsArt photo editing and anti-hoax apps. Two communities are chosen; they are GBI Bethel in Bandung and GPIB Karunia in Tangerang. While the benefits of this community service (1)with this digital communication knowledge and skill, older people maintains their health physically, mentally and cognitively (2)older people become creative and independent and (3)this workshop aims to eliminate the gap between digital natives and digital immigrants in order to excel communication between generations. The results of this training, older people understand how digital technology can maintain their health and the fact that they are becoming fluent in using digital media. Issues being addressed in this activity are related to SDG number 3 and 10.